Composition of the essential oil of two Salvia taxa (Salvia sclarea and Salvia verticillata subsp. verticillata) from Turkey. (2015) - Dogan, Gulden; Hayta, Sukru; Yuce, Ebru; Bagci, Eyüp
No abstract available